Análise cienciométrica do efeito de borda e dinâmica florístico-estrutural entre interior e borda em Florestas Estacionais Semideciduais - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The objective was to conduct a scientometric analysis on the edge effect and point out how many meters into the forest the edge effect affects tree vegetation, with the hypothesis that 40 meters indicates the edge in Semideciduous Seasonal Forests of the Cerrado biome. For the scientometric analysis, the Web of Science database was used. The filtering was carried out for documents classified as "scientific articles" in the "forestry" citation area, in the period from 2001 to 2022. 475 publication records were obtained, in which several parameters were analyzed, including number of authors, words in the title, keywords, references, citations, pages and country of publication. Using the free software VOSviewer and PAST, maps were created that cover information on production and citation, keywords, cluster analysis (Gower) and analysis of main components. It was observed that the United States leads in number of publications and citations, followed by Brazil and Australia. There has been an increase over the years in research related to this topic. The keywords demonstrated co-occurrence over time, with emphasis on "fragmentation", "conservation", "habitat fragmentation", "vegetation" and "diversity". For field evaluation, 3 forest remnants were evaluated, which are integrated into agricultural activity zones in the municipality of Ipameri, Goiás, through the forest inventory, carried out in 2017 (T0) and the second period, in 2023 (T1). In area 1, there was a notable transition in phytophysiognomy, migrating from the semi-deciduous seasonal forest to a Cerradão formation, indicating significant environmental changes associated with anthropogenic factors, such as fires and agricultural activities. In area 2, the maintenance of forest formation was indicated by the phytosociological values found and by the dynamics rates. Finally, in area 3, significant changes were observed at the forest edge, while the interior remained stable, highlighting the importance of considering not only the vegetation dynamics within the forest. The distance of 40 meters to determine the edge in semideciduous seasonal forests proved to be adequate.
Keywords: Fragmentos florestais; Borda florestal; Floresta Atlântica; Diversidade; Forest fragments; Forest edge; Atlantic forest; Diversity; RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL